Epidemiological and awareness study of tuberculosis in Batu Pahat, Johor, Malaysia - Sanusi, Shuaibu Babaji (2014)
Tuberculosis (TB) remains one of the serious infectious diseases and has been characterized worldwide as an epidemic by World Health Organization (WHO). TB is still a public health problem in Malaysia. Baseline information on the disease situation is one of the prerequisites for the development of appropriate control measures. The cornerstone in proper management of TB patients is ensuring high awareness in communities about TB. Thus the current research is directed to investigate the epidemiology of TB, determined the level of public awareness of TB and some factors that are responsible for the emergence of TB. Retrospective method was used for collecting epidemiological data from the Batu Pahat chest clinic. All registered TB patients (total of 1213 patients) from 2008 to 2013 in Batu Pahat Chest Clinic were included in the study. On the other hand, the awareness study was carried out by the use of questionnaires. A two-stage cluster sampling method was used. 600 respondents were targeted which form the study sample. However, 498 questionnaires were returned. Descriptive data analysis was employed to describe the results in frequency and percentage distribution. It was discovered that there was an annually increase in TB incidence with pulmonary TB the most common infection in Batu Pahat. Almost all (92.7%) the TB cases were new. On the other hand, majority (87.0%) of respondents have heard about TB. Common symptoms identified by respondents were coughing for over 2 weeks (51.8%), hemoptysis (49.2%) and difficulty in breathing (50.2%). Smoking cigarette (74.3%), living with individual having chronic cough (71.5%) and HIV/AIDS (65.7%) were the common risk factors of TB identified by respondents. Most of the respondents (83.5%) were aware of the existence of TB drugs. However, the standard DOTs treatment duration of 6-9 months was identified by few (12.4%) respondents. This research provided information regarding TB status in Batu Pahat. The level of awareness among Batu Pahat general public about TB is fairly good. Meanwhile, more need to be done especially on diabetes as the risk factors of TB and treatment duration.